Analisis Proses Penetrasi Sosial dalam Membangun Hubungan Interpersonal melalui Fitur Telepath Aplikasi Omi : Studi Kasus Masyarakat di Kelurahan Margahayu, Bekasi Timur - Fitri Nuraini; Mareta Puri Rahastine; Anggie Ayu Astria Latuperrisa (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study aims to understand how users of the OMI app build interpersonal closeness and engage in self-disclosure through the Telepath feature. The OMI app is a digital dating platform used within the social circles of the Margahayu neighborhood in East Bekasi. Through the Telepath feature, users can chat via anonymous voice calls within a specific time limit, so that their physical appearance is not visible when a new conversation begins The theory used to support this research is the Social Penetration Theory by Irwin Altman and Dalmas Taylor. This study was designed using a descriptive qualitative method with a case study approach to capture the users’ perspectives. All data were collected through observation, in-depth interviews with five active user informants, and supplemented with documentation. The research findings indicate that the communication among the five informants progressed through the stages of a relationship, starting from anonymous introductions, moving to in-depth conversations, and culminating in the decision to share real photos each other. However, the level of intimacy achieved was not always the same; the majority of informants were able to advance their closeness to a more personal level such as exchanging personal contact information or meeting in person, while others had to stop due to various obstacles.